2023
DOI: 10.3390/cells12182209
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Roles of Protein Palmitoylation in Cancer Progression, Immunity, Stemness, and Beyond

Mingli Li,
Leisi Zhang,
Chun-Wei Chen

Abstract: Protein S-palmitoylation, a type of post-translational modification, refers to the reversible process of attachment of a fatty acyl chain—a 16-carbon palmitate acid—to the specific cysteine residues on target proteins. By adding the lipid chain to proteins, it increases the hydrophobicity of proteins and modulates protein stability, interaction with effector proteins, subcellular localization, and membrane trafficking. Palmitoylation is catalyzed by a group of zinc finger DHHC-containing proteins (ZDHHCs), whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 216 publications
0
2
0
Order By: Relevance
“…Intriguingly, cathepsins are also known to be overexpressed and associated with poor clinical outcome in pediatric [25]. Recent studies have suggested potential role for S-palmitoylation in lysosomal functions indirectly through its effects on proteins involved in lysosomal tra cking, membrane fusion, signaling pathways and protein degradation [39]. Hence, inhibition of FASN can downregulate CTSZ, which then leads to a reduced degradation of c-Kit and p-c-Kit.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, cathepsins are also known to be overexpressed and associated with poor clinical outcome in pediatric [25]. Recent studies have suggested potential role for S-palmitoylation in lysosomal functions indirectly through its effects on proteins involved in lysosomal tra cking, membrane fusion, signaling pathways and protein degradation [39]. Hence, inhibition of FASN can downregulate CTSZ, which then leads to a reduced degradation of c-Kit and p-c-Kit.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of these disruptions includes changes in membrane dynamics and protein localization, which are critical in cellular signaling and initiating apoptosis. Additionally, anomalies in ZDHHC enzyme function have been associated with the proliferation of cancer characteristics, including unrestrained cell growth, invasion, and metastasis [121]. These findings underscore the enzymes' dual capacities as potential oncogenes or tumor suppressors, contingent on the biological context, and spotlight the therapeutic promise of targeting palmitoylation pathways to restore regulated cell death and combat cancer progression [111,122].…”
Section: Linking Palmitoylation To Cellular Death In Cancermentioning
confidence: 97%